2022
DOI: 10.1021/acsphotonics.1c01577
|View full text |Cite
|
Sign up to set email alerts
|

Metasurface-Dressed Two-Dimensional on-Chip Waveguide for Free-Space Light Field Manipulation

Abstract: We show that a metasurface-coated two-dimensional (2D) slab waveguide enables the generation of arbitrary complex light fields by combining the extreme versatility and freedom on the wavefront control of optical metasurfaces with the compactness of photonic integrated circuits. We demonstrated offchip 2D focusing and holographic projection with our metasurfacedressed photonic integrated devices. This technology holds the potential for many other optical applications requiring 2D light field manipulation with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…The flatness of metalens makes it feasible to manufacture compact and integrated optical systems. , Although the number of publications on beam focusing on the broadband spectrum has rapidly increased during the past decade, its progress toward commercial devices such as a tunable zoom lens in the camera is still lagging behind anticipation. The challenges typically come from the limited dynamic control mechanism and the slow response speed, which hinder its integration into an imaging system to replace the traditional zoom lens array.…”
Section: Applicationsmentioning
confidence: 99%
“…The flatness of metalens makes it feasible to manufacture compact and integrated optical systems. , Although the number of publications on beam focusing on the broadband spectrum has rapidly increased during the past decade, its progress toward commercial devices such as a tunable zoom lens in the camera is still lagging behind anticipation. The challenges typically come from the limited dynamic control mechanism and the slow response speed, which hinder its integration into an imaging system to replace the traditional zoom lens array.…”
Section: Applicationsmentioning
confidence: 99%
“…Shaping the free-space emission from a silicon photonic chip to create a focused beam has been achieved with different approaches [ 18 , 73 , 74 , 75 , 76 , 77 ]. Beam focusing allows optical excitation or sensing exclusively of a small volume in the space, which is critical for quantum computation with ion qubits [ 18 ], optical tweezers [ 78 ], optogenetics [ 17 ], FPA-based beam steerers [ 44 ], and microscopy.…”
Section: Beam Shapingmentioning
confidence: 99%
“…In the work by Yulaev et al [ 73 ], the authors added a metalens on top of the 2D beam expander demonstrated in [ 70 ], as shown in Figure 10 d. Working on the SiN platform, they generated a focused spot with a diffraction-limited size of 473 nm at the wavelength of 780 nm. Such a metasurface approach was pushed a step forward by integrating metasurfaces monolithically on silicon waveguides [ 75 ]. An OPA can also be designed to emit a focused beam, as demonstrated by Notaros et al (see Figure 10 e,f) [ 76 ].…”
Section: Beam Shapingmentioning
confidence: 99%
“…Metasurface-based applications are promising alternatives to replacing existing optical devices, owning to the ultrathin, ultracompact, and multifunctional properties of meta-devices based on the principles of meta-optics [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ]. Meta-optics offer the possibility to address the limitations of conventional optics and a new paradigm to achieve on-chip integrated meta-devices with multi-functional and parallel control of light beams [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. Optical metalenses are predicted to have the potential to produce disruptive applications due to the integration of advanced imaging, and the miniaturization and multi-dimensional manipulation of meta-optics [ 126 , 127 , 128 , 129 , 130 ].…”
Section: Introductionmentioning
confidence: 99%